TWSC at Forty: Multidisciplinary Research and the Challenges to the Center - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 32 No 1,2 (2017): TWSC and Forty Years of Critical Scholarship, 2018)
Notes from the editor on this special issue on the commemoration of the fortieth anniversary of the University of the Philippines Third World Studies Center.